Kajian Yuridis Terhadap Penerbitan Surat Perintah Penyidikan Ganda - Vivi Angely Ririhena; John Dirk Pasalbessy; Jacob Hattu (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: An Investigative Order or Sprindik is one of the legal processes related to administration in giving authority to investigators to be able to carry out investigations.Purposes of the Research: To analyze and discuss whether it is justified in terms of criminal procedural law procedures, issuance of investigative orders (sprindiks) on the same legal subject with different objects and to explain what legal consequences occur when two sprindiks are issued from the same subject, in the case of BNI Ambon branch main office in 2019. Methods of the Research: The research method used is normative juridical research. In this study, three approaches to the problem are used, namely the statutory approach, the conceptual approach, and the case approach. Sources of data obtained are primary legal materials and secondary legal materials. The technique of collecting legal materials uses the literature study method. All data in this study were analyzed qualitatively.Results of the Research: The results of this study indicate that the rules regarding the issuance of the Sprindik are in accordance with the provisions of the criminal procedure law but there are no rules that specifically regulate the number of times the Sprindik is issued by investigators. In a criminal case, the issuance of the double Sprindik resulted in the abuse of power (abuse of power), conflict of interest among investigators, and the cancellation of the Sprindik through the pretrial process and the existence of the Double Sprindik resulted in the absence of legal certainty regarding which Sprindik was used. This is because there are no regulations that explicitly regulate the number of times the Sprindik is issued.